A facile route to synthesize n-SnO2/p-CuFe2O4 to rapidly degrade toxic methylene blue dye under natural sunlight. Issue 26 (6th June 2022) - Duan, Kaijiao; Que, Tingting; Koppala, Sivasankar; Balan, Ramdas; Lokesh, Budigi; Pillai, Rahul; David, Selvaraj; Karthikeyan, Parasuraman; Ramamoorthy, Sangeetha; Lekshmi, I. C.; Kemacheevakul, Patiya; Padmavathy, Nagarajan; et al.
Abstract : The synthesis of n-SnO2 /p-CuFe2 O4 to degrade toxic methylene blue dye under natural sunlight and its mechanism. Abstract : In the present study, the n-SnO2 /p-CuFe2 O4 (p-CFO) complex was prepared by a two-step process. p-CFO synthesized by the molten salt method was coated with SnO2 synthesized by a facile in situ chemical precipitation method. The formation of n-SnO2 /p-CFO was confirmed by powder X-ray diffraction (PXRD). Scanning electron microscopy (SEM) images showed that the sharp edges of uncoated pyramid-like p-CFO particles were covered by a thick layer of n-SnO2 on coated p-CFO particles. The complete absence of Cu and only 3 wt% Fe on the surface of the n–p complex observed in the elemental analysis using energy-dispersive X-ray spectroscopy (EDX) on the n–p complex confirmed the presence of a thick layer of SnO2 on the p-CFO surface. Diffuse reflectance spectroscopy (DRS) was employed to elucidate the bandgap engineering. The n-SnO2 /p-CFO complex and p-CFO showed 87% and 58.7% methylene blue (MB) degradation in 120 min under sunlight, respectively. The efficiency of the n–p complex recovered after 5 cycles (73.5%) and was found to be higher than that of the uncoated p-CFO (58.7%). The magnetically separable property of the n–p complex was evaluated by using vibration sample magnetometry (VSM) measurements and it was confirmed that the prepared photocatalyst can be easily recovered using an external magnet. The study reveals that the prepared complex could be a potential candidate for efficient photodegradation of organic dyes under sunlight due to its efficient recovery and reusability owing to its magnetic properties.